Relações pressão-diâmetro e esforço-diâmetro do ventrículo esquerdo em seres humanos. Padronização e análise crítica do método. - Matsubara, B. B.; Bregagnollo, E. A.; Ribeiro, M. A.; Tucci, P. J. (My University, 1990)
PURPOSE--To provide a critical analysis of the fluid filled manometric system and M-mode echocardiography and, by their association, to standardize the determination of left ventricular (LV) pressure-diameter and stress-diameter relationships in humans. MATERIAL AND METHODS--The pressure curve and the LV M-mode image was obtained in 24 patients with cardiopathy. The dynamic characteristics of the fluid-filled system have been studied to define the amplitude, the resonance and the time gap of the pressure curve register. The delay of the pressure curve recording was determined in all cases by comparing pressure curve and echocardiographic aortic valve registers. The values of pressure, diameter, posterior wall thickness and LV meridional stress was calculated at every 0.02s. RESULTS--Preliminary analyses of the fluid-filled manometric system indicated that this system has variable dynamic characteristics. The pressure-diameter and stress-diameter loops obtained were similar to those of the literature. The values of end-systolic stress, percentage of fractional shortening, ejection fraction and circumferential fiber shortening rate of patients with dilated cardiomyopathy (n = 5) were significantly reduced when compared to the values of patients without left ventricular overload (n = 8) and patients with ventricular volume overload. It has been verified, also, that the retard of the pressure curve record introduced by the fluid-filled manometric system does not modify the values of these variables. CONCLUSION--The LV pressure-diameter and stress-diameter relationships obtained by the association of echocardiography and LV manometry showed functional characteristics of the ventricle that could not appear by the use of the echocardiography or by the LV manometry themselves.
Left ventricular pressure-diameter and stress-diameter relations in humans. Standardization and critical analysis of the method
Keywords: blood pressure; echocardiography; heart disease; heart stroke volume; heart ventricle; human; manometry; methodology; pathology; pathophysiology; review; Blood Pressure; Echocardiography; English Abstract; Heart Diseases; Heart Ventricle; Human; Manometry; Stroke Volume